Efficacy of Danlou tablets in patients with acute coronary syndrome undergoing percutaneous coronary intervention: a multicenter prospective cohort study - Cai, Yajie; Yang, Qiaoning; Xi, Ruixi; Yang, Furong; Gu, Feng; Zhao, Yang; Guo, Ming; Dong, Guoju; Gao, Zhuye; Fu, Changgeng; Wang, Peili; Du, Jianpeng; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Danlou tablets (DLTs) have been widely used to treat coronary heart disease in China. However, the benefits associated with DLT for patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) in routine practice require further investigation. Purpose To investigate the effectiveness of DLT in patients with ACS undergoing PCI. Methods This multicenter prospective cohort study for patients with ACS undergoing PCI was conducted in 40 centers in mainland China from February 2012 to December 2018. This trial is registered under ChiCTR-OOC-14005552. Patients were assigned to either the DLT group or the conventional medicine (CM) group based on whether they used DLT prior to enrollment. The duration of DLT use (1.5 g, three times a day) was 12 months. The primary endpoint comprised of cardiac death, non-fatal myocardial infarction, and urgent revascularization. Secondary endpoint included rehospitalization owing to ACS, heart failure, stroke, and other thrombotic events. The Seattle Angina Questionnaire (SAQ) was used to assess quality of life (QOL). Primary and secondary endpoints were followed up for 36 months, and the SAQ was followed up for 12 months. The Cox proportional hazards regression model was used to analyze the independent effect of DLT on primary and secondary endpoints. Propensity score matching (PSM) analyses were performed to mitigate bias. Survival estimation was performed using Kaplan–Meier survival curves and log-rank tests in the PSM cohort, and landmark analyses were used for further evaluation of primary and secondary endpoints. Subgroup analyses and interactions confirmed the robustness of the findings. Linear mixed effects models were used to assess the QOL. Results Overall, 936 patients were enrolled in this cohort study, of whom 875 completed follow-up. The primary and secondary endpoints had no significantly difference between the DLT and CM groups after Cox proportional hazards models. Kaplan–Meier survival curves and log-rank tests performed in the PSM cohort also found no significant differences between the two groups on primary and secondary endpoints. However, landmark analysis showed significant benefit in the primary endpoint for the DLT group after 200 days (hazard ratio [HR] 0.46, 95% confidence interval [CI] 0.22–0.93, P = 0.03). Landmark analysis also showed a significant benefit in the secondary endpoint in the DLT group within 200 days (HR 0.33, 95% CI 0.15–0.73, P = 0.006). Moreover, DLT improves the SAQ summary score, and scores in the physical limitation, treatment satisfaction, and disease perception domains for patients with ACS undergoing PCI. Conclusions DLT combined with conventional treatment reduced the risk of the primary endpoint after 200 days and the secondary endpoint within 200 days during the 3-year follow-up. Additionally, DLT can improve the QOL without adverse effects.